(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2023)
The agriculture economic viability is a result of a correct planning and knowledge of the crop production environment. The level of meteorological information in the region can be improved through the water balance, making the agricultural planning more accurate. The objective of this study was to characterize the West of the São Paulo State through the agrometeorological water balance. Historical daily data from 1992 to 2021, from the meteorological station of the University of West Paulista in Presidente Prudente, São Paulo, were used in the study. The sequential water balance (deficit and excess of water in the soil) was evaluated during the agricultural season (from October to March) and off-season (from April to September). The annual water deficit was -303.2 mm, being -125.2 mm in the agricultural season and -178.0 mm in the off-season. The frequent occurrence of deficit in the region, in the beginning of spring and mainly during the autumn-winter, makes it necessary to adopt special management practices and to use irrigation in order to reach high agricultural productivity in West Paulista.